MULTIOBJECTIVE APPROACH FOR POWER FLOW AND UNBALANCE CONTROL IN LOW-VOLTAGE NETWORKS CONSIDERING DISTRIBUTED ENERGY RESOURCES - Ferreira, W. M.; Brandao, D. I.; Guimaraes, F. G.; Tedeschi, E.; Marafao, F. P. [UNESP]; IEEE (Ieee, 2017)
This paper proposes a multiobjective optimization technique that maximizes the active power generation from single-phase distributed generators, and minimizes the unbalance factor at the point of common coupling of the network. Such technique is incorporated into a centralized control strategy for optimal power flow control purpose. The centralized control strategy used herein is the Power-Based Control that coordinates the distributed units to contribute to the network's active and reactive power needs, per phase, in proportion of their power capacity. The simulation results of a simplified network with three single-phase distributed generators validate the proposal in terms of power flow control, voltage regulation and power quality.
Keywords: Distributed generation; Genetic algorithm; Microgrid; Multiobjective power flow; Unbalance